2008
DOI: 10.1016/j.jinteco.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Human capital and wages in exporting firms

Abstract: This paper studies the link between a …rms education level, export performance and wages of its workers. We argue that …rms may escape intense competition in international markets by using high skilled workers to di¤erentiate their products. This story is consistent with our empirical results. Using a very rich matched worker…rm longitudinal dataset we …nd that …rms with high export intensities pay higher wages. However, an interaction term between export intensity and skill intensity has a positive impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
110
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 34 publications
9
110
0
1
Order By: Relevance
“…Schank et al (2007) find that the exporting wage premium almost vanishes when worker characteristics are controlled for. Munch and Skaksen (2008) find that the level of firms' export intensity is not significant when an interaction between this and firm skill intensity is included. They conclude that the export premium only accrues to firms with high human capital.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Schank et al (2007) find that the exporting wage premium almost vanishes when worker characteristics are controlled for. Munch and Skaksen (2008) find that the level of firms' export intensity is not significant when an interaction between this and firm skill intensity is included. They conclude that the export premium only accrues to firms with high human capital.…”
Section: Introductionmentioning
confidence: 72%
“…Still, the exporter wage premium remains unchanged. Using data for Denmark, Munch and Skaksen (2008) have argued that the export premium is only significant for firms with high skill intensity. They show this by including an interaction term between average education in the firm and export intensity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, even if there is a positive effect of working in an exporting firm on well-being and involvement at work, this effect will probably be captured by measures of worker's human capital and compensation since it has been shown that human capital intensity and average wages in exporting firms are higher than in non-exporting firms (e.g., Munch and Skaksen, 2008). Noteworthy, as indicated previously, we included variables measuring education levels, seniority and wage as control variables.…”
Section: The Empirical Modelmentioning
confidence: 99%